Pengaruh Profitabilitas, Risiko Bisnis, dan Growth Opportunity Terhadap Struktur Modal - Wulan Aprilla; Kusuma Wijayanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Capital structure is the composition of financing used by companies to meet their expenditure needs, consisting of a combination of long-term internal and external funds. The purpose of this study is to determine the effect of profitability, business risk, and growth opportunity on the capital structure of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2021-2024. This study applies secondary data and a quantitative approach with data processing using SPSS version 27 and multiple linear regression analysis. The research sample was selected using purposive sampling. A total of 41 companies that met the criteria produced 163 observations from a total population of 98 companies. The analysis shows that the variables of profitability, business risk, and growth opportunity have a significant effect on capital structure. These three variables collectively explain 53.8% of the variation in capital structure, while the rest is influenced by factors outside the scope of this study.